Psychological Well-Being And Work Motivation Amongst Medical Professionals - Rehman, Ghazala; Malik , Najma Iqbal; Taj , Rizwan (Journal of Pakistan Psychiatric Society, 2006)
Objective: The study examines the relationship of psychological well-being and work motivation in asample of Pakistani medical professionals.Design: Cross sectional comparative study.Place and duration of the study: The study was conducted in private (Alshifa International Hospital,Islamabad, and Islamabad Private Hospital) and public sector hospitals (Pakistan Institute of medicalSciences and Rawalpindi General Hospital) in the twin-cities of Islamabad and Rawalpindi, Pakistan during 2002.Subjects and Methods: A sample of 120 medical professionals belonging to the private and publicsector hospitals (n=60 in each) participated in the study. They were selected on the basis of purposiveconvenient sampling technique. The data was collected with the help of Psychological Well-Being Scale(Wb) and Work Preference Inventory (WPI) and a separately devised demographic sheet containing information about age, experience and private and public sector affiliation.Results: The age range of the sample was between 30-60 years (M=42.97, SD=7.96). The range ofexperience in service was 1-42 years (M=16.28, SD=8.43). Scores of psychological well being had asignificant inverse co-relation with extrinsic motivation (r=-0.26, p < .01). Public and private sectordoctors showed a highly significant difference in their motivational orientation (p < .01). The relation ofage with scores of well being and motivation showed a significant difference, (t=3.9, p<.001) and (t=2.41,p<0.05) between those aged 53 and above and those 41 years of age or less respectively.Conclusion: Compared to the private sector, the environment of public sector is perceived to be morechallenging. Similarly, older medical professionals seem to be having higher psychological well-beingand work motivation, compared to the younger medical professionals. However, these findings suggestthe need for further exploration of some interrelated variables, which might give us insight for futurepolicy implementation, suggesting ways for further improvement in the psychological facets of the workenvironment of this dynamic group of professionals.Key words: Psychological well-being, Work Motivation, Intrinsic Motivation, Extrinsic Motivation, MultipleOccupational Roles (MOR).